2018
DOI: 10.1371/journal.pone.0207776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transcriptionally regulated genes identifies NCOR1 in hormone receptor negative breast tumors and lung adenocarcinomas as a potential tumor suppressor gene

Abstract: Regulation of transcription is a key process in cellular homeostasis. It depends on regulators that either repress or stimulate the transcription of genes, therefore controlling different biological functions. The Nuclear Receptor Corepressor 1 (NCOR1) is one of those co-repressors that regulate the transcription by facilitating the recruitment of HDAC1, 2, 3, 4, 5 and 7. In our article, by using an in silico approach, we evaluate the mutational status of NCOR1 in breast and lung tumors. We identified that NOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Thus, we hypothesized that NCOR1 is associated with the specific antitumor effect of TNFα. Indeed, the role of NCOR1 in cell proliferation and cancer development has been described in previous reports [ 39 , 40 , 41 , 42 ], and our data showed that NCOR1 knockdown selectively suppressed the proliferation of ERα-positive cells in vitro and tumor growth in vivo. Consistently with the specific pro-proliferative function of NCOR1, NCOR1 knockdown induced apoptosis selectively in ERα-positive but not in ERα-negative breast cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, we hypothesized that NCOR1 is associated with the specific antitumor effect of TNFα. Indeed, the role of NCOR1 in cell proliferation and cancer development has been described in previous reports [ 39 , 40 , 41 , 42 ], and our data showed that NCOR1 knockdown selectively suppressed the proliferation of ERα-positive cells in vitro and tumor growth in vivo. Consistently with the specific pro-proliferative function of NCOR1, NCOR1 knockdown induced apoptosis selectively in ERα-positive but not in ERα-negative breast cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…NCOR1 is a transcription factor that regulates various biological functions ( 61 ). As a tumor suppressor gene, mutation in NCOR1 was confirmed to be associated with the prognostic prediction of numerous cancers, such as breast cancer, lung adenocarcinoma and GISTs ( 62 , 63 ). These findings suggest that NCOR1 mutations are a potential biomarker for the molecular diagnosis and prognosis of osteosarcoma.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the difference between the proportion of stage IV patients may contribute to the difference in the KM analysis. Mutations or deletions of NCOR1 have been described in bladder cancer ( 30 ). Thus, deep deletions of NCOR1 have been taken into account.…”
Section: Resultsmentioning
confidence: 99%